Employee Engagement as Mediator Between Talent Management, Employer Branding, and Employee Retention - Indah Aripah, Fadilah Dwi; Misbahuddin Azzuhri (UPT Publikasi Ilmiah Unisba, 2025)
The objective of this quantitative study is to investigate the mediating role of employee engagement in the effects of talent management and employer branding on employee retention. Using census sampling, all 84 employees of Department of Human Resources, Organization, and Culture at the Financial Services Authority were involved as the research respondents. The data was harvested via Google Forms and analyzed using Structural Equation Modeling in Smart PLS 3.0, following the evaluation of the measurement model, structural model, hypothesis testing, and mediation testing. This study finds that talent management has a positive and insignificant effect on employee retention, that employer branding has a positive and significant effect on employee retention, and that employee engagement mediates the effect of talent management and employer branding on employee retention.